2012
DOI: 10.1016/j.rmed.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in interstitial lung disease: Prevalence, prognosis and 6 min walk test

Abstract: PH occurred in 14% of a cohort of patients with ILD and was associated to IPF and lower lung function parameters. Mortality was markedly higher in PH patients, and the presence of PH reduced 6MWT independently of lung function and the presence of IPF. The present results emphasize the need for intensified treatment of patients with ILD and PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 29 publications
6
101
3
2
Order By: Relevance
“…In general, the prevalence of PH was similar in studies from Europe [18,25,[40][41][42][43][44][45][47][48][49], North America [5,6,26,28,46,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], Asia and Africa [37,[68][69][70][71][72][73][74][75], although the majority of evidence was reported from North America (n=23, 53%). Across studies, the prevalence of PH among IPF patients ranged from 3% to 86%; most estimates tended to be between 30% and 50% (figure 3) [25, 43, 44, 47, 50, 52-66, 68, 71-73].…”
Section: Pulmonary Hypertensionmentioning
confidence: 85%
“…In general, the prevalence of PH was similar in studies from Europe [18,25,[40][41][42][43][44][45][47][48][49], North America [5,6,26,28,46,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], Asia and Africa [37,[68][69][70][71][72][73][74][75], although the majority of evidence was reported from North America (n=23, 53%). Across studies, the prevalence of PH among IPF patients ranged from 3% to 86%; most estimates tended to be between 30% and 50% (figure 3) [25, 43, 44, 47, 50, 52-66, 68, 71-73].…”
Section: Pulmonary Hypertensionmentioning
confidence: 85%
“…In CF, one study reported moderate relationships between 6MWD and FEV1 (r50.53) and FVC (r50.62) [67]. In PAH, correlations between 6MWD and mean pulmonary artery pressure ranged from -0.2 to -0.62 [43,63,68,69].…”
Section: Is the 6mwt A Maximal Test?mentioning
confidence: 99%
“…14 studies included patients with COPD [109][110][111][112][113][114][115][116][117][118][119][120][121][122], eight studies included patients with ILD [69,[123][124][125][126][127][128][129], nine studies included patients with PAH [43,[130][131][132][133][134][135][136][137] and four included studies patients with other chronic respiratory disease or on the list for transplantation [138][139][140][141]. Average 6MWD at baseline was between 300 and 450 m ( fig.…”
Section: Relationship Of 6mwd To Clinical Outcomesmentioning
confidence: 99%
“…5 A study from Denmark reported pulmonary hypertension in 14% with mixed types of ILD and who were screened for PH by echocardiography and concluded that 8% of them had mild PH (Mean PAP >25 mmHg, but <35 mmHg) and 6% of them had severe PH (Mean PAP >35 mmHg). [23][24] Hamada et al observed that the prevalence of PH in this patient population was as low as 8.1%. 25 Abeles AM et al reported that C-Reactive Protein was raised in 45.2% cases and was the most consistent finding followed by serum ANA positivity in 17.8% cases (Maximum in IPF: 27.6%) and also found that Serum DsDNA was positive in 6.9% cases with IPF and 20% in CTD associated ILDs.…”
Section: Resultsmentioning
confidence: 68%